2020
DOI: 10.3390/su12041330
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Criteria Assessment Procedure for Outdoor Lighting at the Design Stage

Abstract: This paper presents an attempt at a unified approach for the assessment of outdoor lighting solutions at the design stage. First of all, the lighting criteria for different types of outdoor lighting installations have been carefully described. Despite the differences in criteria, it is possible to find a common ground for the assessment of lighting solutions at the design stage. This is based on the need for the assessment of lighting solutions to be included in the requirements for the luminous environment, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…These parameters are subject to standardization restrictions. It is also possible to check the energy efficiency of the design by calculating the utilisation factor [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are subject to standardization restrictions. It is also possible to check the energy efficiency of the design by calculating the utilisation factor [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…A study that suggested a decision supporting systems' assessment for street lighting restricted the assessment to light pollution and energy performance indicators [16]. Another study that presented a multicriteria assessment with the aim of finding the most beneficial and sustainable lighting solution used indicators representing the luminous environment, light pollution, and energy efficiency to evaluate four groups of outdoor lighting types [17]. A third study, which aimed to propose a method for assessing public tenders of LED lighting based on multiple decision-making criteria, restricted the environmental impact assessment evaluation to life cycle analysis (LCA) [18].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe (EU28) there are more than 1.6 million km of illuminated streets that annually consume approximately 35 TWh) at a cost of $4 billion euro for the public authorities [2]. During the last decade there has been ongoing research activity focused on energy management using various types of renewable energy sources [3][4][5], on recycling [6], on safety [7][8][9][10], and a concentrated effort has been made for making street lighting systems sustainable [11][12][13][14][15][16][17][18][19] and environmentally friendly [20][21][22]. In addition, during the last few years, the issue of avoiding light pollution [23][24][25][26][27][28] has gained importance in technical reports [29] and expert discussions [30].…”
Section: Introductionmentioning
confidence: 99%